(untitled) (Journal of history, 2024)
Korean cartography has a fifteen-century tradition, dating back to the Three Kingdoms period (from the 1st century BC to the 7th century AD). Korean cartography was greatly influenced by neighboring China, with which Korea had engaged in scientific exchange for thousands of years. In 1392, the power of the Joseon Dynasty was established throughout the Korean Peninsula, in which Korean cartographers created maps of the country and its eight provinces, as well as maps of the world and China. Depicting China on world maps, the Koreans also designated the territories of their western neighbors (the peoples of the Great Steppe), Turkic cities, Central Asia, mountains, rivers, etc. With the penetration of Western scientific thought into China and the Korean Peninsula, round maps of the world are being distributed on their territories instead of rectangular ones. This article is devoted to the study of geographical names of the Great Steppe in Chinese and Korean on maps of the world and China of the Middle and New Ages. In the course of the research, the authors for the first time identified numerous toponyms and hydronyms of the Great Steppe on five Korean maps, in particular the geographical designations: “Turkestan” and “Kazakhs”.